Vote Leave and Take Back Control: Examining Ethically Questionable Marketing in the Leave.eu Campaign. - Wong, Antonia (2017)
This research explores the ethicality of the marketing employed by the Leave.eu campaign in the 2016 EU Referendum. It illuminates voter-centric perceptions of such marketing and ascertains what issues the campaign sought to communicate to the public, if it was effective in this regard and whether they were ethically marketed. A blend of qualitative research methods: discourse analysis of three televised debates broadcasted in the run-up to the Referendum and ten semi-structured interviews are utilised to achieve these research aims. The findings illustrate that Leave.eu projected a nationalistic campaign ideology through morally ambiguous marketing. This research argues that voters identify such unethical marketing within the campaign and consequently generalise it to the practice overall, highlighting a macro problem of increasing distrust towards the discipline and supporting previous research. This thesis aims to contribute to growing bodies of literature regarding marketing in British politics and negative conceptions of the overall practice.